(untitled) (Analysis in Theory and Applications, 2016)
This paper is part II of "On Copositive Approximation in Spaces of Continuous Functions". In this paper the author shows that if Q is any compact subset of real numbers, and M is any finite dimensional strict Chebyshev subspace of C(Q), then for any admissible function fC(Q)M, the best copositive approximation to f from M is unique.